2018
DOI: 10.21277/sw.v2i8.331
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem of Teens with Visual Impairments as a Predictor of Hardiness

Abstract: <p>The paper discusses the problem of visually impaired teens’ hardiness and its predictors. The results shows that teenagers with visual impairments do not differ from “healthy” peers in terms of hardiness, however, their self-esteem is different to teens with normal vision. Predictors of hardiness are: idealized representations of own health and well-being for blind adolescents; actual self-esteem of happiness and persprctive self-esteem for teenagers with low vision; actual self-esteem of happiness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Berdasarkan hasil kategorisasi teoritis, subjek dalam penelitian ini memiliki selfesteem dengan tingkatan tinggi sebanyak 36 orang dengan persentase 56,3% dan dengan tingkatan sedang sebanyak 28 orang dengan persentase 43,8%, sehingga dapat disimpulkan mayoritas partisipan yaitu remaja tunanetra di Bali memiliki self-esteem yang tinggi. Sejalan dengan penelitian sebelumnya yaitu penelitian oleh Miklyaeva & Gorkovaya (2018) yang menunjukkan bahwa remaja tunanetra memiliki self-esteem lebih tinggi jika dibandingkan dengan remaja yang sehat atau awas serta penelitian e-ISSN: 2622-464x https://journal-psikologi.hangtuah.ac.id 104 lain oleh Salehi et al (2015) pada individu tunanetra yang menunjukkan sebanyak 65,2% dari 138 partisipan memiliki skor self-esteem yang tinggi.…”
Section: Diskusiunclassified
“…Berdasarkan hasil kategorisasi teoritis, subjek dalam penelitian ini memiliki selfesteem dengan tingkatan tinggi sebanyak 36 orang dengan persentase 56,3% dan dengan tingkatan sedang sebanyak 28 orang dengan persentase 43,8%, sehingga dapat disimpulkan mayoritas partisipan yaitu remaja tunanetra di Bali memiliki self-esteem yang tinggi. Sejalan dengan penelitian sebelumnya yaitu penelitian oleh Miklyaeva & Gorkovaya (2018) yang menunjukkan bahwa remaja tunanetra memiliki self-esteem lebih tinggi jika dibandingkan dengan remaja yang sehat atau awas serta penelitian e-ISSN: 2622-464x https://journal-psikologi.hangtuah.ac.id 104 lain oleh Salehi et al (2015) pada individu tunanetra yang menunjukkan sebanyak 65,2% dari 138 partisipan memiliki skor self-esteem yang tinggi.…”
Section: Diskusiunclassified
“… Augestad (2017) did a systematic review on 26 relevant studies between 1998 and 2016 and pointed out that research results were divergent regarding whether the visually impaired would show lower level of self-esteem than the sighted, several factors such as social support, gender, and parenting seemed important for their self-esteem development; however, longitudinal studies are warranted to draw conclusions about causal effects. It is generally acknowledged that adolescents with visual impairment face great challenges to obtain high levels of self-esteem ( Miklyaeva and Gorkovaya, 2018 ), although they may or may not show lower levels of self-esteem than sighted adolescents. A recent study reported that over 90% of students with visual impairment in regular schools in Tanzania had high self-esteem ( Kapinga and Aloni, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Miklyaeva and Gorkovaya (2019) consider that "the hardiness of visually impaired adolescents and its components (commitment, control and challenge) do not differ from similar indicators in the sample of their 'healthy' peers. Probably, the development of ideas about one's own life and relationships with the world happens in accordance with the universal laws of personal formation regardless of the vision status in adolescence."…”
Section: Introductionmentioning
confidence: 99%